Development of home appliances controller with DTMF signal - Ahmad Nawir, Nur Amalina; Mohd Isira, Ahmad Sadhiqin; Basari, Amat Amir; Mohamed Yunus, ‪Noor Azlina (Penerbit Universiti Teknikal Malaysia Melaka, 2019)
This paper presents the development of home appliances controller design that utilizes Dual-Tone Multi Frequency (DTMF) signal from the landline telephone. The device contains microcontroller that links with a decoder IC that converts DTMF signal into binary codes and vice versa. It is proven that the device enables residents to send and receive signal from outside the house; thus enabling them to control the appliances at home. Finally, the results from an experimental setup found that the device is proven to be working.